2022
DOI: 10.3389/fneur.2022.882991
|View full text |Cite
|
Sign up to set email alerts
|

40 Hz Blue LED Relieves the Gamma Oscillations Changes Caused by Traumatic Brain Injury in Rat

Abstract: BackgroundPhotobiomodulation (PBM) using low-level light-emitting diodes (LEDs) can be rapidly applied to various neurological disorders safely and non-invasively.Materials and MethodsForty-eight rats were involved in this study. The traumatic brain injury (TBI) model of rat was set up by a controlled cortical impact (CCI) injury. An 8-channel cortex electrode EEG was fixed to two hemispheres, and gamma oscillations were extracted according to each electrode. A 40 hz blue LED stimulation was set at four points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Studies have shown that hippocampal gamma oscillations could be modulated by 40 Hz light flicker and then involved in the process of cognitive ability 10,11,22,23 . Previous study found that gamma oscillations of the injury side after TBI in rats is decreased, and 40 Hz light flicker could attenuate the down‐regulation of gamma oscillation after TBI 24 . Thus, we suspected that gamma oscillations, which could be affected by 40 Hz light flicker, is manipulated and then involved in the process of cognitive ability after TBI treatment in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that hippocampal gamma oscillations could be modulated by 40 Hz light flicker and then involved in the process of cognitive ability 10,11,22,23 . Previous study found that gamma oscillations of the injury side after TBI in rats is decreased, and 40 Hz light flicker could attenuate the down‐regulation of gamma oscillation after TBI 24 . Thus, we suspected that gamma oscillations, which could be affected by 40 Hz light flicker, is manipulated and then involved in the process of cognitive ability after TBI treatment in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite such variability, EEG recordings in mild-TBI patients revealed a significant decrease in synchronization of the low gamma band frequency (25 Hz−40 Hz) across the scalp when compared to healthy controls ( Wang et al, 2017 ). Similarly, a recent study showed decreased gamma power in rat models of TBI in which case 40 Hz visual entrainment by blue LED light could revive gamma power in the injury side of the brain in order to improve overall prognosis ( Yang et al, 2022 ). Therefore, it is highly likely that the propagative nature of sensory entrainment may be suitable for a lesion-diverse condition like TBI, and it could also be remarkably beneficial in terms of scavenging hyper-phosphorylated tau protein and Aβ clusters, thus having significant prognostic value.…”
Section: Opportunities Aheadmentioning
confidence: 96%